Descriptions and records of the Palaearctic Molophilus Curtis (Diptera, Limoniidae) - Starý, Jaroslav (Zootaxa, 2011)
Seven new species of Molophilus (Molophilus) are described, viz. M. (M.) creticola sp. n. (Greece (Crete)), M. (M.) cypricola sp. n. (Cyprus), M. (M.) carbonis sp. n. (Portugal), M. (M.) hradileki sp. n. (Kazakhstan), M. (M.) brevifurcatus sp. n. (Czech Republic, Slovakia), M. (M.) calabricus sp. n. (South Italy), and M. (M.) suboccultus sp. n. (Portugal). Lackschewitz’s (1940a) “varieties” obscura of M. (M.) propinquus (Egger, 1863) and testacea of M. (M.) griseus (Meigen, 1804) are elevated to species rank and redescribed, and a new replacement name, ibericus nom. n., is proposed for the former species. Lectotypes are designated for M. (M.) nigrescens Lackschewitz, 1940, M. (M.) ibericus nom. n., and M. (M.) pleuralis de Meijere, 1920, and the male terminalia are redescribed for M. (M.) nigrescens. All important characters are illustrated. New records of some other Molophilus (Molophilus) species are appended.